2015
DOI: 10.1007/s00428-015-1860-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated 4E-binding protein 1 expression is associated with poor prognosis in small-cell lung cancer

Abstract: Phosphorylation of eukaryotic translation initiation factor 4E (eIF4E) binding protein (4E-BP1) results in release of eIF4E, which sequentially relieves translational repression and enhances oncogenic protein synthesis. We assessed the expression of phosphorylated 4E-BP1 (p-4E-BP1) in small-cell lung cancer (SCLC) and its correlation with clinicopathological factors and patient survival. This study included 117 SCLCs, which comprised 108 primary and 9 metastatic tumor tissues. We performed immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
4
11
0
Order By: Relevance
“…We showed that the levels of these factors (p4E‐BP1, peIF4E) increase during tumor progression and that peIF4E, age, and histologic grade were independent prognostic factors in the multivariate analysis. These results are consistent with those of previous studies in several types of carcinomas, where p4E‐BP1, eIF4E, and peIF4E were overexpressed, associated with a poorer prognosis, and considered critical “funnel factors” in cell signaling .…”
Section: Discussionsupporting
confidence: 92%
“…We showed that the levels of these factors (p4E‐BP1, peIF4E) increase during tumor progression and that peIF4E, age, and histologic grade were independent prognostic factors in the multivariate analysis. These results are consistent with those of previous studies in several types of carcinomas, where p4E‐BP1, eIF4E, and peIF4E were overexpressed, associated with a poorer prognosis, and considered critical “funnel factors” in cell signaling .…”
Section: Discussionsupporting
confidence: 92%
“…4E‐BP1 is a negative regulator of protein translation in mammalian cells and can be inactivated by p‐mTOR, which promotes its dissociation from eIF‐4E. Dephosphorylated 4EBP1 combines with eIF‐4E and inhibits the initiation of translation in the presence of mTOR inhibitors . Our results show that SCU suppresses pan‐AKT, mTOR, and p‐mTOR, and increases 4EBP1 significantly, indicating that the anticancer effects of SCU might be linked to inactivation of the AKT/mTOR/4EBP1 pathway.…”
Section: Discussionmentioning
confidence: 64%
“…EIF4EBP1, a critical regulator of MTOR downstream signaling, may be associated with drug resistance in human tumors (70). Phosphorylation of EIF4EBP1 results in release of EIF4E, which enhances the oncogenic protein synthesis and correlates with the poor prognosis in lung cancer (71,72). …”
Section: Discussionmentioning
confidence: 99%